Improved Unlike-Particle Collision Operator for delta-f Drift-Kinetic Particle Simulations (Communications in Computational Physics, 2018)
Plasmas in modern tokamak experiments contain a significant fraction ofimpurity ion species in addition to main deuterium background. A new unlike-particlecollision operator for δf particle simulation has been developed to study the nonlocaleffects of impurities due to finite ion orbits on neoclassical transport in toroidalplasmas. A new algorithm for simulation of cross-collisions between different ionspecies includes test-particle and conserving field-particle operators. An improvedfield-particle operator is designed to exactly enforce conservation of number, momentumand energy.